1992
DOI: 10.1177/00220345920710030801
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Oxygen Consumption in Dog Gingiva during Induction of Experimental Periodontitis

Abstract: The purpose of this study was to examine changes in oxygen consumption in dog gingiva during induction of experimental periodontitis. The disease was induced in adult mongrel dogs during a 16-week period by placement of silk ligatures around selected teeth. The oxygen consumption rate of gingival tissue was determined in vivo by a non-invasive technique, tissue reflectance spectrophotometry. Changes in such clinical parameters as gingival index, plaque index, pocket depth, attachment level, and gingival crevic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
2
6
1
Order By: Relevance
“…None of the histological samples in this study showed any evidence of periodontal destruction, such as loss of connective tissue attachment, or inflammation infiltration into the attachment or alveolar bone. Although they contrast with the findings of previous studies using the silk‐ligature‐induced periodontitis model in various animals, 7,9,12 the present results can be interpreted based on host susceptibility 26 and periodontal pathogenesis based on dysbiosis in the ecological plaque hypothesis 29,30 . Also from a clinical standpoint, periodontitis cannot be induced by a single factor of microbiological loading 31 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…None of the histological samples in this study showed any evidence of periodontal destruction, such as loss of connective tissue attachment, or inflammation infiltration into the attachment or alveolar bone. Although they contrast with the findings of previous studies using the silk‐ligature‐induced periodontitis model in various animals, 7,9,12 the present results can be interpreted based on host susceptibility 26 and periodontal pathogenesis based on dysbiosis in the ecological plaque hypothesis 29,30 . Also from a clinical standpoint, periodontitis cannot be induced by a single factor of microbiological loading 31 .…”
Section: Discussioncontrasting
confidence: 99%
“…Several periodontitis models have been widely used in research evaluating the effects of specific treatments, including the ligature model and the addition pathogenic bacteria. [7][8][9][10][11][12][13] However, in another animal study, the longstanding accumulation of dental plaque in a silk-ligature model induced a restricted area of inflammation around both teeth and the installed dental implants in dogs. 4,5 In addition, the causality and progression of periodontitis remain unclear, and the characteristics of periodontitis need to be inferred from clinical observations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the increased oxygen consumption in moderately infiamed gingivae (Glickman et al 1949. Zajicek & KindJova 1972, Hanioka et al 1992), In the present study, toothbrushing increased the Hb oxygen saturation ill inflamed gingivae nearly to the level found in healthy gingivae before brushing. This might help to relieve gingival inflammation, because Hb oxygen saturation increases as gingival inflammation decreases (Hanioka et al, 1991), However, since the present study dealt only with the immediate effect of toothbrushing on oxygen sufficiency in gingiva.…”
Section: Discussionsupporting
confidence: 64%
“…Increase in biood supply in inflamed gingiva may be insufficient to meet the oxygen demand in dogs, (Hanioka et al, 1992) and humans (Hanioka et al, 1990), In the present study, improvement in microcirculatory function was found after mechanical stimulation even in the presence of supragingival plaque. Similar effect on gingival microcirculatorv function was also found itnmediately after mechanical stimulation (Tanaka et al, 1997), Thus, the acute effect on gingival microcircuiation evoked repeatedly may contribute to the observed improvement in inflamed gingiva, Gingival fluid and gingival tissues provided the pocket environment with oxygen (Mettraux et al, 1984), The oxygen environment in the pocket may depend upon the oxygen tension in the gingival tissue.…”
Section: Discussionsupporting
confidence: 50%